Strategi Pemberitaan Injil Melalui Komunitas Sel di Mahanaim Community Church Semarang - Kirana Luhur, Chandra (P3M STT Kristus Alfa Omega, 2024)
This research identifies that personal evengelism by the servant of God through a multiplicative cell community model is less than optimal because the member of cell group have difficulty building a thriving community, as evidenced by the absence of new members. The purpose of the study was to describe the personal evangelism model through cell communities for cell group of Mahanaim Community Church Semarang to develop future church leaders using qualitative methods. The results of interviews and observations show several barriers that hinder the growth of cell communities. To overcome these barriers, an inclusive approach and awareness of the role of each member in supporting the growth of the community are needed